(untitled) (International Journal of Current Engineering and Technology, 2015)
This paper presents the kinetic adsorption of maltose from aqueous solution onto granular activated carbon (GAC). Attempts have been conducted experimentally by shaking different GAC samples doses (5, 10 and 30 g/l) with 6000 mg/l maltose concentration solution for 8 hr at different shaking speed values (45,100 and145 rpm). The adsorption kinetic models; Pseud first order, pseud second order, intra-particle diffusion and mass transfer models were used for analyzing the kinetic of maltose sorption by GAC. The findings indicates that maltose sorption onto GAC is well represented by the pseud second order model.